The Orphan Response Regulator Aor1 Is a New Relevant Piece in the Complex Puzzle of Streptomyces coelicolor Antibiotic Regulatory Network - Antoraz, Sergio; Rico, Sergio; Rodríguez, Héctor; Sevillano, Laura; Alzate, Juan F.; Santamaría, Ramón I.; Díaz, Margarita (Frontiers in Microbiology, 2017)
Streptomyces coelicolor, the best-known biological antibiotic producer, encodes 29 predicted orphan response regulators (RR) with a putative role in the response to environmental stimuli. However, their implication in relation to secondary metabolite production is mostly unexplored. Here, we show how the deletion of the orphan RR Aor1 (SCO2281) provoked a drastic decrease in the production of the three main antibiotics produced by S. coelicolor and a delay in morphological differentiation. With the aim to better understand the transcriptional events underpinning these phenotypes, and the global role of Aor1 in Streptomyces, a transcriptional fingerprint of the ∆aor1 mutant was compared to a wild-type strain. RNA-Seq analysis revealed that the deletion of this orphan regulator affects a strikingly high number of genes, such as the genes involved in secondary metabolism, which matches the antibiotic production profiles observed. Of particular note, the sigma factor SigB and all of the genes comprising its regulon were up regulated in the mutant. Our results show that this event links osmotic stress to secondary metabolite production in S. coelicolor and indicates that the RR encoded by aor1 could be a key regulator in both of these processes.